UPLC-Q–TOF–MS, network analysis, and molecular docking to investigate the effect and active ingredients of tea-seed oil against bacterial pathogens - Duan, Yan; Zhao, Li-Juan; Zhou, Yan-Hui; Zhou, Qi-Zhi; Fang, Ai-Qing; Huang, Yu-Ting; Ma, Yuan; Wang, Zhi; Lu, Yu-Ting; Dai, Yu-Ping; Li, Shun-Xiang; Li, Juan (Frontiers in Pharmacology, 2023)
Object: This research intended to probe the antibacterial effect and pharmacodynamic substances of Tea-Seed Oil (TSO) through the use of ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS) analysis, network analysis, and molecular docking. Methods: The major chemical components in the methanol-extracted fractions of TSO were subjected to UPLC-Q-TOF-MS. Network pharmacology and molecular docking techniques were integrated to investigate the core components, targets, and potential mechanisms of action through which the TSO exert their antibacterial properties. To evaluate the inhibitory effects, the minimum inhibitory concentration and diameter of the bacteriostatic circle were calculated for the potential active ingredients and their equal ratios of combinatorial components (ERCC) against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans. Moreover, the quantification of the active constituents within TSO was achieved through the utilization of high-performance liquid chromatography (HPLC). Results: The methanol-extracted fractions contained a total of 47 chemical components, predominantly consisting of unsaturated fatty acids and phenolic compounds. The network pharmacology analysis and molecular docking analysis revealed that various components, including gallocatechin, gallic acid, epigallocatechin, theophylline, chlorogenic acid, puerarin, and phlorizin, have the ability to interact with critical core targets such as serine/threonine protein kinase 1 (AKT1), epidermal growth factor receptor (EGFR), a monoclonal antibody to mitogen-activated protein kinase 14 (MAPK14), HSP90AA1, and estrogen receptor 1 (ESR1). Furthermore, these components can modulate the phosphatidylinositol-3-kinase protein kinase B (PI3K-AKT), estrogen, MAPK and interleukin 17 (IL-17) signaling pathways, hereby exerting antibacterial effects. In vitro validation trials have found that seven components, namely gallocatechin, gallic acid, epigallocatechin, theophylline, chlorogenic acid, puerarin, and phloretin, displayed substantial inhibitory effects on E. coli, S. aureus, P. aeruginosa, and C. albicans, and are typically present in tea oil, with a total content ranging from 15.87∼24.91 μg·g−1. Conclusion: The outcomes of this investigation possess the possibility to expand our knowledge base concerning the utilization of TSO, furnish a theoretical framework for the exploration of antibacterial drugs and cosmetics derived from inherently occurring TSO, and establish a robust groundwork for the advancement and implementations of TOS products within clinical settings.